Analysis of Debt Restructuring Methods for Negative Equity Firm - Ikhsan Abi Nubli; Viverita (Future Science, 2020)
This paper aims to find the best debt restructuring methods for negative equity firms. This study uses four common debt restructuring methods, i.e. Debt-to-Equity swaps, debt-to-asset swaps, issuing convertible bonds, and repayment agreements. Furthermore, based on each debt structure, we compared their price-to-book ratio and debt-to-equity ratio (DER) to find the best possible method for every firm and their industries. The sample for this study is firms listed on the Indonesia Stock Exchange (IDX). The ideal capital structure of the firms is deter-mined by using an iterative algorithm. After finding their ideal capital structure, firms will be treated by debt restructuring to reach their ideal capital structure. Mostly, firms are better performances while using debt to an equity swap and issuing convertible bonds. This condition is proven by increasing their P/BV and their better capital structure by looking at their DER. Furthermore, a debt to asset swap is better to use for firms with high DER. Whilst debt repayment agreements do not affect the firm’s capital structure and its value.